Characterization of benzenemethanethiol in sesame-flavour baijiu by high-performance liquid chromatography-mass spectrometry and sensory science. (1st December 2021) - Wu, Ziyang; Qin, Dan; Duan, Jiawen; Li, Hehe; Sun, Jinyuan; Huang, Mingquan; Sun, Baoguo
Highlights: An efficient method for the determination of benzenemethanethiol in sesame-flavoure baijiu was established. The method of derivatization reaction made the quantification more accurate. Benzenemethanethiol had an important contribution to the aroma of sesame-flavor baijiu. Abstract: Chinese sesame-flavour baijiu (CSB) is one of aroma types discovered after the founding of China. Sulfur-containing compounds have low content in CSB but play an important role. This study developed a quantitative method by derivatization reaction combined LC-MS/MS for the determination of benzenemethanethiol (BM), which has a roasted aroma in CSB. Under the optimized conditions, the LOD and LOQ of BM were 11.73 ng L −1 and 39.09 ng L −1, respectively. The recovery yield of the derivatization product ranged from 82.12% to 93.99%. The content of BM in 4 CSBs were 150.22–860.40 ng L −1 . To confirm the contribution of BM to the overall aroma of CSB, aroma recombination experiments and omission experiments were carried out. Compared with that of the simulated baijiu sample without BM, the roasted aroma of the simulated baijiu sample containing BM was enhanced. Omission experiments showed that BM made important contributions to the overall aroma of CSB.